Dynamic interaction between the two-axle vehicle and continuous girder bridge with considering vehicle braking force - Nguyen Xuan Toan (Vietnam Journal of Mechanics)
Nowadays, the structures of continuous girder bridges are becoming more and more popular with the rapid development of highway networks in many nations around the world, including Vietnam. High strength materials are commonly used to construct the bridge structures, so they are very slender and sensitive to the effects of dynamic loads, especially in the cases that vehicles run with high speed or brake suddenly on the bridges. In this paper, the author would like to introduce the study of a model of dynamic interaction between two-axle vehicle and continuous girder bridge. The model of a two-axle vehicle consists of three masses, taking into account the inertia force and friction force between the tires and the bridge surface due to vehicle braking. Vertical reaction forces of axles which change with time make bending vibration of beam increase significantly. The results of the experiment on the Hoaxuan Bridge and the analysis of the computerized model indicate that dynamic factors are substantial when vehicle brakes suddenly on bridge.